Professional Knowledge Management Third Biennial Conference, WM 2005, Kaiserslautern, Germany, April 10-13, 2005, Revised Selected Papers - Althoff, Klaus-Dieter.; Dengel, Andreas; Bergmann, Ralph; Nick, Markus; Roth-Berghofer, Thomas; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2005)
Professional knowledge management is imperative for the success of enterprises. One decisive factor for the success of knowledge management projects is the coordination of elements such as corporate culture, enterprise organization, - man resource management, as well as information and communication techn- ogy. The proper alignment and balancing of these factors are currently little understood$1 (Bespecially the role of information technology, which is often - garded only as an implementation tool, though it can be a catalyst by making new knowledge management solutions possible. This conference brought together representativesfrom practical and research ?elds for discussing experiences, professional applications, and visions through presentations, workshops, tutorials, and an accompanying industry exhibition. The main focus of the conference was the realization of knowledge mana- ment strategies with the aid of innovative information technology solutions, such as intelligent access to organizational memories, or integration of business processes and knowledge management. Also of interest were holistic/integrative approaches to knowledge management that deal with issues raised by the in- gration of people, organizations, and information technology.s
Keynote Contributions -- Intelligent Office Appliances (IOA) -- Learning Software Organizations (LSO) -- Learner-Oriented Knowledge Management and KM-Oriented E-Learning (LOKMOL) -- Peer-to-Peer and Agent Infrastructures for Knowledge Management (PAIKM) -- Knowledge Intensive Business Processes (KiBP) -- German Workshop on Experience Management (GWEM) -- Knowledge Management in Medicine (KMM) -- Knowledge Management in International Professional Services Firms (KMIPSF) -- Knowledge Management for Distributed Agile Processes: Models, Techniques, and Infrastructure (KMDAP) -- Knowledge Management and Business Intelligence (KMBI) -- Intelligent IT Tools for Knowledge Management Systems: (KMTOOLS 2005) -- Semantic Model Integration (SMI) -- Workshop on Philosophy and Informatics (WSPI) -- Workshop on Information Just-in-Time (WIJIT) -- Knowledge Management in Small and Medium Enterprises (WMKMU).
Keywords: Computer science; Information storage and retrieval; Artificial intelligence; Application software; Education -- Data processing; Computer Science; Artificial Intelligence (incl. Robotics).; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Computer Appl. in Administrative Data Processing; Computers and Education; Electronic books